(v-7)(v+7)=x

Simple and best practice solution for (v-7)(v+7)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-7)(v+7)=x equation:


Simplifying
(v + -7)(v + 7) = x

Reorder the terms:
(-7 + v)(v + 7) = x

Reorder the terms:
(-7 + v)(7 + v) = x

Multiply (-7 + v) * (7 + v)
(-7(7 + v) + v(7 + v)) = x
((7 * -7 + v * -7) + v(7 + v)) = x
((-49 + -7v) + v(7 + v)) = x
(-49 + -7v + (7 * v + v * v)) = x
(-49 + -7v + (7v + v2)) = x

Combine like terms: -7v + 7v = 0
(-49 + 0 + v2) = x
(-49 + v2) = x

Solving
-49 + v2 = x

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + v2 = 49 + x

Combine like terms: -49 + 49 = 0
0 + v2 = 49 + x
v2 = 49 + x

Simplifying
v2 = 49 + x

Reorder the terms:
-49 + v2 + -1x = 49 + x + -49 + -1x

Reorder the terms:
-49 + v2 + -1x = 49 + -49 + x + -1x

Combine like terms: 49 + -49 = 0
-49 + v2 + -1x = 0 + x + -1x
-49 + v2 + -1x = x + -1x

Combine like terms: x + -1x = 0
-49 + v2 + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| 4x+7x+9x=60 | | 16h+2=8h+78 | | 16x+2=19x-7 | | 3+4=2.4 | | 4(x^2-2)=0 | | 3x-9=4-3x | | p=6-3/4q | | 8(4x-7)-(x-3)=7(x+7)+5 | | 7=a+3 | | x^2+8x=2x | | =10+7q-3r+2q-r | | 5(-3)+2=4(2y+5) | | 12+5x=19+2x | | Sin*4x+sin*6x=0 | | 4(x+6)=10x-36 | | z/8-1=9 | | x^2+100x=24 | | (-15m+2)(15-2)=0 | | 8h-11=16 | | 1/x-1/(x-5)=9/100 | | 12(x-4)=9 | | (y-8)(y+8)=63 | | -2n-12p= | | -2n+22=4p | | 4(x-2)=3(x+10) | | 7=10e-4f | | -1/2x2-3 | | 7-5e=4f-34 | | 7-5e=rf-34 | | 3y-5y=5y+1 | | -3r+6u+10r-9u= | | 9m-8t=56 |

Equations solver categories